An outbreak of Burkholderia cepacia bloodstream infections in a tertiary-care facility in northern India detected by a healthcare-associated infection surveillance network. (7th March 2023) - Fomda, Bashir; Velayudhan, Anoop; Siromany, Valan A.; Bashir, Gulnaz; Nazir, Shaista; Ali, Aamir; Katoch, Omika; Karoung, Alphina; Gunjiyal, Jacinta; Wani, Nayeem; Roy, Indranil; VanderEnde, Daniel; et al.
Abstract: Objective: The burden of healthcare-associated infections (HAIs) is higher in low- and middle-income countries, but HAIs are often missed because surveillance is not conducted. Here, we describe the identification of and response to a cluster of Burkholderia cepacia complex (BCC) bloodstream infections (BSIs) associated with high mortality in a surgical ICU (SICU) that joined an HAI surveillance network. Setting: A 780-bed, tertiary-level, public teaching hospital in northern India. Methods: After detecting a cluster of BCC in the SICU, cases were identified by reviewing laboratory registers and automated identification and susceptibility testing outputs. Sociodemographic details, clinical records, and potential exposure histories were collected, and a self-appraisal of infection prevention and control (IPC) practices using assessment tools from the World Health Organization and the US Centers for Disease Control and Prevention was conducted. Training and feedback were provided to hospital staff. Environmental samples were collected from high-touch surfaces, intravenous medications, saline, and mouthwash. Results: Between October 2017 and October 2018, 183 BCC BSI cases were identified. Case records were available for 121 case patients. Of these 121 cases, 91 (75%) were male, the median age was 35 years, and 57 (47%) died. IPC scores were low in the areas of technical guidelines, human resources, and monitoring and evaluation. Of the 30 environmental samples, 4 grew BCC. A single source of the outbreak was not identified. Conclusions: Implementing standardized HAI surveillance in a low-resource setting detected an ongoing Burkholderia cepacia outbreak. The outbreak investigation and use of a multimodal approach reduced incident cases and informed changes in IPC practices.